Editorial - Fernando, Marrisa (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
This issue of the ABAC ODI Journal Vision. Action. Outcome. presents ten articles on various topics highlighting change management in various contexts . There are five action research papers that present the use of organization development interventions in five different institutions of higher education, four papers on challenges in the hotel , tourism , and service industry, and a model development research.